Effects of the protein source and content in milk replacers on bone and organ growth in lambs artificially reared from birth until six weeks of age : a thesis presented in partial fulfilment of the requirements for the degree of Master in Animal Science at Massey University, Palmerston North, New Zealand - Desesquelles, Solene Nathalie Stephanie (Massey University, 2024)
The objective of this study was to investigate if preweaning diets differing in protein source and content altered growth rates as well as bone and organ development in lambs artificially reared from birth until six weeks of age. Lambs removed within the first 48 hours from the dam were randomly allocated to one of the two rearing treatments; MP: milk-protein based milk replacer or WVP: whey and vegetable-protein based milk replacer. Four lambs from each treatment were slaughtered at two weeks of age while the remaining lambs were slaughtered at six weeks of age. Lamb live weight at two weeks of age did not differ (p > 0.05) between treatments. There were differences in bone morphology and organ growth, although milk protein-based milk replacer (MP) was associated with greater lamb live weight and average daily gain at six weeks of age (p < 0.05). From birth until six weeks of age, the type of milk replacer had no effect on stature measures and bone morphology (p > 0.05), meaning that early lamb bone growth is influenced by increases in live weight rather than the type of milk replacer used. Lamb development is driven by live weight gain however, lambs were observed only from birth until six weeks of age, which has limited the observation of live weight gain and thus, changes in bone morphology and organ weight. The differences in the preweaning diets may have altered the future developmental potential growth of bone and organs in lambs but this needs further investigation.
Keywords: 300301 Animal growth and development